Relationship of Parents' Social Support with the Self-Concept of Poor Students - Ervina Rianti; Firman Firman (Jurnal Neo Konseling, 2020)
Poor students who have economic limitations have a variety of financial obstacles in living life. The reality is that there are still many underprivileged students with low self-concept. Self-concept is a perspective that every individual has about themselves, including their strengths and weaknesses, in the form of their knowledge, judgment and expectations about themselves. One factor that is thought to influence the self-concept is the social support they get. This study aims to see how the relationship between parental social support and self-concept of underprivileged students in SMP Negeri 6 Solok City. This type of research uses a quantitative approach with a descriptive correlational method, with a sample of 61 underprivileged students of SMP Negeri 6 Solok City, using the Purposive Sampling technique. The instrument used in this study was a questionnaire distributed via the Google forms application. by referring to the Likert Scale. Data were analyzed with descriptive statistical techniques and Pearson Product Moment Correlation techniques with the help of the SPSS program. The results of this study reveal that: (1) Social support of underprivileged parents in general is in the high category with a frequency of 42,62295%, (2) The self-concept of underprivileged students in general is in the medium category with a frequency of 40.98361, (3) There is a significant positive relationship between parental social support and self-concept of underprivileged students with a correlation coefficient of 0.586 with a significance level of 0,000.